Information System Website-Based Profile of the Ibnu Nadzir Education Foundation with NLP Implementation for Smart FAQ - Moh. Harun Arrosyid; Novi Hendri Adi; Alex Sandri Sikumbang; Yera Wahda Wahdi (International Journal Labs, 2026)
The rapid advancement of information technology has significantly transformed how educational institutions disseminate information to the public. Yayasan Pendidikan Ibnu Nadzir (YPIN), a character-based educational foundation in Batam City, Indonesia, still relies on brochures and verbal communication as its primary means of information dissemination. This approach leads to difficulties in accessing complete institutional information, a weak professional image, and recurring repetitive questions from prospective students' guardians. This study aims to design, implement, and evaluate a website-based profile information system for YPIN integrated with Natural Language Processing (NLP) to enable a Smart FAQ feature. The system was developed using the Agile Development method, encompassing iterative stages including requirements analysis, system design, development, testing, deployment, and review. The system design utilized UML diagrams, Entity Relationship Diagrams (ERD), and user interface mockups. The Smart FAQ feature was implemented using a text preprocessing pipeline consisting of case folding, cleansing, normalization, tokenizing, stopword removal, and stemming, followed by TF-IDF weighting and Cosine Similarity for measuring question-answer relevance. The system was successfully deployed on the domain ypin.or.id using PHP 8.7, MySQL, and HTTPS-secured hosting. Functional testing achieved 100% success, Smart FAQ accuracy reached 76%, and content validity by information system experts yielded a Content Validity (CV) score of 1.00, indicating very valid results. A user acceptance evaluation involving 18 respondents produced an average Likert score of 4.49, categorized as Excellent. These results demonstrate that the developed system effectively addresses the identified problems and improves information services and institutional professionalism at YPIN.